0127 Sociodemographic, Socioeconomic, and Behavioral Correlates of Nightmare Frequency in a Community Sample. (12th April 2019) - Lane, Elizabeth; Ellis, Jason; Killgore, William D S; Warlick, Chloe; Alfonso-Miller, Pamela; Grandner, Michael A
Abstract: Introduction: Nightmares are important sleep problems that are related to depression and suicide risk. This analyses examined whether sociodemographic, socioeconomic, and physical/mental health factors predict nightmare frequency, as well as beliefs/attitudes about sleep. Methods: Data were from the Sleep and Healthy Activity, Diet, Environment, and Socialization (SHADES) study. N=986 adults age 22-60 provided complete data. Nightmare frequency was assessed as Never, Seldom (1/year), Sometimes (1/month), or Often (1/week or more). Sociodemographics included age (by decade), sex, and race/ethnicity. Socioeconomic included education, ability to afford the basics, and Subjective Social Status (SSS). Other variables included overall health, social support, control over sleep, whether work responsibilities, home/family responsibilities, mood, and feeling unsafe affects sleep, and depression score (PHQ-9). Ordinal logistic regressions were adjusted for age/sex/education. Results: In adjusted models, increased nightmare frequency was associated with sociodemographics, including age in the 40s (OR=2.4, p<0.0005) or 50s (OR=2.2, p<0.0005), being female (OR=1.3, p=0.04), and having less education (some college OR=1.4, p=0.02; high school OR=1.6, p=0.04), and decreased frequency was seen in Blacks/African-Americans (OR=0.6, p=0.001). Regarding socioeconomics, increased nightmare frequency was seen among those who found it difficult (OR=1.6, p=0.01) or very difficult (0R=1.7, p=0.006) to afford the basics, or had lower subjective social status (OR=1.2, p<0.0005). More nightmares were also seen among those whose health was rated fair (OR=1.9, p=0.002) or poor (OR=2.5, p<0.0005). Fewer nightmares were seen in those with more self-rated control over sleep (OR=0.9, p<0.0005) and greater social support (OR=.97, p<0.0005) and more were seen in those who felt that their sleep environment was unsafe (OR=2.0, p<0.0005) or who believed that their sleep quality was adversely affected by work (OR=1.4, p=0.01) or mood (OR=2.1, p<0.0005), or who had higher depression scores (OR=1.1, p<0.0005). Conclusion: Nightmares are clinically relevant and are related to a wide range of demographic, socioeconomic, health-related, and sleep-related factors. Support (If Any): R01MD011600, R21ES022931